(untitled) (American Journal of Islam and Society, 2006)
On January 9, 2006, in Washington, DC, the Saban Center for Middle East Policy at the Brookings Institution hosted the highest level meeting between the Bush administration and the American Muslim community. Entitled “Bridging the Divide?” and organized by the Brookings Project on US Policy toward the Islamic World, representatives of various Muslim organization were granted the opportunity to interface with C. David Welch, the Assistant Secretary of the Bureau of Near Eastern Affairs. The conference, a follow-up to previous initiatives on “Bridging the Divide” theme, sought to bring together key leaders and specialists “to explore the potential space for the American Muslim community to assist and advance US policy towards the Islamic world and capabilities within the community that might be better tapped.” In attendance were representatives from the American government, officials from a variety of American Muslim organizations, American Muslim foreign policy experts, others from the Washington thinktank and policy communities, and students. In the opening speech, Welch acknowledged several unique characteristics about the American Muslim community: its integration into American civic life; being Americans as well as Muslims; and, despite post-9/11 tensions, steering a moderate course while confronting extremist Islamist tendencies. As evidence, he cited the Fiqh Council of North America’s recent fatwa against Islamic terrorism that was endorsed by major Muslim organizations. He recognized that American Muslims can play an exceptional role in explaining the American position, given their cultural, linguistic, and ethnic ties with the Islamic world, and acknowledged the history of conflict between the United States and the Muslim world. In addition, he condemned the seeming “civilizational strife” between Islam and the West as a pointless “jihad/crusade.” He stated that he was more comfortable with the relationship of the United States with the Muslim – especially Arab – world as being defined by a dialog stressing the commonalities of belief in God, virtue, family life, and socioeconomic justice ...